Faktor-Faktor Yang Berhubungan Dengan Kelengkapan Pendokumentasian Di Rumah Sakit Swasta X Di Batam - Sindi Hairuna Batubara; Utari Christya Wardhani; Sri Muharni (Lembaga Pengembangan Kinerja Dosen, 2024)
Nursing documentation is a legal aspect that protects nurses in providing nursing services, but documentation is still found to be incomplete. This research aims to determine the factors that influence the completeness of documentation at the X Batam private hospital. The method in this research uses a total sampling technique with Quantitative research method with a cross sectional design. The sample consisted of 30 respondents. The data was processed using the chi square test. Based on gender characteristics, there were 7 respondents male and 23 female respondents, and based on the education level of Bachelor of Nursing, there were 27 respondents and D3 of nursing. as many as 3 respondents. Univariate analysis Motivation was mostly in the strong category with a presentation of 83.3%, knowledge was mostly in the good category with a presentation of 90.0%, workload was mostly in the low category with a presentation of 76.7%, documentation was mostly in the good category with a presentation of 80.0%. Bivariate analysis of factors influencing completeness of documentation. P-Value 0.001 (<0.005). It was concluded that motivation, knowledge and workload factors showed a significant relationship with completeness of documentation. It is hoped that more nursing documentation good again.